Pertumbuhan dan Hasil Jamur Tiram Pada Berbagai Komposisi Media Tanam - Nurul Istiqomah; Siti Fatimah (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2014)
Oyster mushrooms usually can growth at any planting medium, are naturally like wood of tree or another medium, such as sawdust, straw, groundsel, waste of sugar cane. That sawdust or straw still need to added with other material, like ricebran, limestones, gypsum, etc. The composition of medium have various formulation. Everyone who cultivate of oyster have special composition for their medium that made from their personal research, e.g the secret of base material, suplement material, and the precisely of mixing. This research has the purpose of (i) knowing of growth and yield of oyster mushroom at various of composition of growing media, and (ii) obtain the best composition of growing media. The research was conducted in the Village of Banjang, Districts of Banjang , HSU and started from March 2012 to June 2012, using a Completely Randomized Design (CRD) one factor. Factors tested were composition of planting media (sawdust : rice bran : limestone : gypsum), ie k1 = 90% : 7,5% : 2% : 0,5%, k2 = 80% : 15% : 4% : 1%, k3 = 70% : 22,5% : 6% : 1,5%, k4 = 60% : 30% : 8% : 2% dan k5 = 50% : 37,5% : 10% : 2,5%. The results showed that the composition of planting media determine of growth and yield of oyster mushroom and the composition of planting media that showing of the best of growth and yield is k3.